Investigation on wear behavior of bamboo filler reinforcement of injection moulded plastic gear - Mehat, N.M. (Trans Tech Publications Ltd, 2017)
An increase in demand for industrial gears has instigated the escalating uses of plastic-matrix composite, particularly carbon or glass fibre reinforced plastics as gear materials to enhance the mechanical strength and thermal resistance of plastic gear. Nevertheless, the production of large quantity of these synthetic fibres reinforced composites has posed serious threat to ecosystem. This study is conducted to study the applicability and practical ability of using bamboo fillers particularly in plastic gear manufacturing as opposed to synthetic fibres. The Taguchi method is used to investigate the effects of gear test rig parameters and bambo filler reinforcement on wear behaviour of injection moulded plastic gear. The results revealed that the use of natural fillers such as bamboo in the plastic gear industry is practical and economically viable. © 2017 Trans Tech Publications.